2011
DOI: 10.1002/app.35152
|View full text |Cite
|
Sign up to set email alerts
|

Morphology evolution of miscible blends between crystalline PA6 and amorphous PA6IcoT

Abstract: ABSTRACT:The morphology evolution of miscible blends of a semicrystalline polyamide 6 (PA6) and an amorphous polyamide 6Ico6T (PA6IcoT) was investigated using an internal Brabender mixer at a temperature range 220-260 C. Morphology of the blends was characterized by scanning electron microscopy (SEM) and laser particle analysis. Temperature rising dissolution was used to separate the different phases of the blends and the phase compositions were determined by Fourier transform infrared (FTIR) spectroscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Cao et al explored the morphology of a PA6I/PA6T copolymer with PA6, in a 90:10 ratio. 48 The blend was divided and classified in three by dissolving it in dimethyl sulfoxide (DMSO) at two different temperatures, 80 and a 100 C: the fraction insoluble at 100 C (PA6), the fraction dissolved at 80 C (PA6I/PA6T) copolymer and the fraction dissolved between the two temperatures. However, a posterior analysis of the filtrates showed that this division was unsuccessful.…”
Section: Structural Conformation Of Ppasmentioning
confidence: 99%
“…Cao et al explored the morphology of a PA6I/PA6T copolymer with PA6, in a 90:10 ratio. 48 The blend was divided and classified in three by dissolving it in dimethyl sulfoxide (DMSO) at two different temperatures, 80 and a 100 C: the fraction insoluble at 100 C (PA6), the fraction dissolved at 80 C (PA6I/PA6T) copolymer and the fraction dissolved between the two temperatures. However, a posterior analysis of the filtrates showed that this division was unsuccessful.…”
Section: Structural Conformation Of Ppasmentioning
confidence: 99%
“…Recently, binary and ternary nanocomposites of aPAs, mainly with elastomers, have also been studied. The blends of aPAs with PA6 were miscible while those with PEI and PAE were compatible . However with polyolefins, EVOH 17 and SAN compatibilizers are required to obtain a minimum compatibility.…”
Section: Introductionmentioning
confidence: 97%
“…These advantages make aPAs commercially attractive and have led to the study of the behavior when blended with many second components. Thus, blends of aPAs with polyesters, PA6, polyolefins, ethylene‐vinyl alcohol copolymer (EVOH), poly(ether imide) (PEI), acrylonitrile‐styrene copolymer (SAN), and poly(amino ether) resin (PAE) have been studied. Recently, binary and ternary nanocomposites of aPAs, mainly with elastomers, have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a melt-mixing process, the exchange reactions may occur between condensing polymer molecules. As a result of exchange reactions, portions of the blends can be transformed into multiblock or random copolymers, which can effectively improve the compatibility of polymers. …”
Section: Introductionmentioning
confidence: 99%